A Meta-Analysis of Organizational Culture and Transformational Leadership Effects on Teacher Performance - Surwiti Surwiti; Widodo Widodo; Sumaryoto Sumaryoto; Hendro Prasetyono (Kuras Institute, 2025)
This study conducts a meta-analysis to examine the effects of organizational culture and transformational leadership on teacher performance across multiple educational contexts. A systematic search was performed through ScienceDirect, Eric, Taylor & Francis, and Google Scholar databases, applying rigorous inclusion criteria for quantitative studies published between 2015 and 2025. From 1250 identified articles, 22 met the eligibility requirements, consisting of 11 studies on organizational culture and 11 on transformational leadership. The random-effects model for organizational culture revealed a significant positive effect on teacher performance (r = 0.448, p < .001), categorized as moderate, though high heterogeneity (I² = 80.18%) indicated contextual variation across studies. In contrast, transformational leadership showed a consistent and significant positive effect (r = 0.441, p < .001) under the fixed-effects model, with low heterogeneity (I² = 4.05%), reflecting stable results across different educational settings. These findings affirm that both organizational culture and transformational leadership are critical determinants of teacher performance, but the influence of organizational culture is more context-dependent. Theoretically, this study enriches the literature on educational management by synthesizing empirical evidence, while practically, it offers insights for policymakers and school leaders in designing strategies to enhance teacher performance through organizational culture development and transformational leadership practices.